Pomegranate seed oil protects against tacrolimus-induced toxicity in the heart and kidney by modulation of oxidative stress in rats - Azar Hosseini; Arezoo Rajabian; Fatemeh Forouzanfar; Mahdi Farzadnia; Mohammad Taher Boroushaki (Mashhad University of Medical Sciences, 2022)
Objective: The clinical use of tacrolimus is limited due to its side effects. This research investigated the protective activities of pomegranate seed oil (PSO) against TAC toxicity.Materials and Methods: The groups are included normal (1 ml of corn oil), TAC (2 mg/kg), and co-treatment of PSO (0.4 and 0.8 ml/kg) and TAC. All administrations were carried out intraperitoneally for 14 days. After the last injection, blood was collected from the heart.Results: TAC increased creatinine and urea. Increased malondialdehyde, reduced thiol content and superoxide dismutase. The elevation of lactate dehydrogenase, aspartate aminotransferase (AST), alanine aminotransferase (ALT), creatinine kinase-MB and creatinine phosphokinase that confirmed cardiac toxicity. PSO reduced TAC toxicity. PSO decreased TAC-induced pathology injury.Conclusion: PSO reduced TAC toxicity in renal and heart via scavenging free radicals.